Hiddensee : a tale of the once and future Nutcracker - Maguire, Gregory (William Morrow, an imprint of HarperCollinsPublishers, 2017)
Gregory Maguire returns with an inventive novel inspired by a timeless holiday legend, intertwining the story of the famous Nutcracker with the life of the mysterious toy maker named Drosselmeier who carves him.--Amazon.com